References of Birth Weights for Gestational Age and Sex from a Large Cohort of Singleton Births in Cameroon - Jean Dupont Kemfang Ngowa; Irénée Domkam; Anny Ngassam; Georges Nguefack-Tsague; Walter Dobgima Pisoh; Cyrille Noa; Jean Marie Kasia (Obstetrics and Gynecology International)
Objective. To establish the percentile charts of birth weights for gestational age and sex within the Cameroonian population. Methods. A review of medical records of infants born between January 2007 and December 2011 at the maternities of two hospitals in Cameroon, Central Africa. Multiple pregnancies, births of HIV infected women, stillbirths, and births with major fetal malformations were excluded. The smooth curves of birth weight for gestational age and sex were created using the Gamlss package under R.3.0.1 software. Results. The birth weights of 12837 live birth singleton infants born to HIV negative women between 28 and 42 weeks of gestation were analyzed to construct the birth weight curves for gestational age and sex. The smoothed percentile curves of birth weights for gestational age and sex of Cameroonian infants have demonstrated an increasing slope until 40 weeks and then a plateau. There was a varied difference of distribution in birth weights for gestational age between Cameroonian, Botswanan, American, and French infants. Conclusion. We established the reference curves of birth weights for gestational age and sex for Cameroonians. The difference in birth weight curves noted between Cameroonian, Botswanan, American, and French infants suggests the importance of establishing the regional birth weight norms.